1955
DOI: 10.1039/jr9550002347
|View full text |Cite
|
Sign up to set email alerts
|

p-Hydroxybenzoate groups in the lignin of aspen (populus tremula)

Abstract: Smith. 2347 p-ljlydroxybenzmte Group8 in the Lipin of Aspen (Populus tremula). By D. C. C. SMITH.[Reprint Order No. 6160.1 They occur singly, involving aliphatic hydroxyl groups of the " native lignin," and account for about 10% of its weight." NATIVE LIGNINS," the soluble analogues of lignins which are the aromatic substances of high molecular weight associated with woodiness in plants (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
1

Year Published

1982
1982
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 0 publications
2
51
0
1
Order By: Relevance
“…The lower absorption coefficient of hardwood MWL at 280nm, as compared to softwood MWL, is attributed to the presence of syringyl groups in the former lignin (9, 10). In hardwoods, lignins show a high absorption coefficient (maximum values in hardwood MWL in Table I), which is attributed to the p-hydroxybenzoate groups in the lignins (13).…”
Section: Chemical Composition Of Exwlmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower absorption coefficient of hardwood MWL at 280nm, as compared to softwood MWL, is attributed to the presence of syringyl groups in the former lignin (9, 10). In hardwoods, lignins show a high absorption coefficient (maximum values in hardwood MWL in Table I), which is attributed to the p-hydroxybenzoate groups in the lignins (13).…”
Section: Chemical Composition Of Exwlmentioning
confidence: 99%
“…The relative intensities of the unconjugated carbony1 bands in aspen EXWL were higher (about two times) than in the aspen MWL (6,13). Based on differential infrared spectra of lignins in woods and pulps, Bolker (15,19) has shown that unconjugated P-ketone groups in isolated lignins are formed during solvolytic isolation.…”
Section: Chemical Composition Of Exwlmentioning
confidence: 99%
“…The lignin of grasses is adorned with g-p-coumarate substituents on a variety of lignin units. Lignin structural analyses of poplar, aspen, willow, and palm have shown that g-p-hydroxybenzoate esters are present (Smith, 1955;Nakano et al, 1961;Sun et al, 1999;Meyermans et al, 2000;Landucci and Ralph, 2001). The fact that only S units are g-p-hydroxybenzoylated in both poplar lignin and the oligolignol fraction supports the contention that sinapyl p-hydroxybenzoate is produced enzymatically and used as an authentic monomer for lignification in poplar.…”
Section: Sinapyl P-hydroxybenzoates Are Precursors In Lignin Biosynthmentioning
confidence: 99%
“…Poplar wood specifically contains p-hydroxybenzoic esters linked to lignin units (Smith, 1955). Alkaline hydrolysis of extract-free samples was performed to determine the impact of the transformation on this acylation.…”
Section: Analysis Of Low-m R Phenolics Released By Mild Alkaline Hydrmentioning
confidence: 99%